Collective Expert Perspectives on the Use of Safinamide as Adjunctive Therapy for Parkinson’s Disease: Online-Based Delphi Survey - Atsushi Takeda; Yoshio Tsuboi; Masahiro Nomoto; Hideki Mochizuki; Nobutaka Hattori (Parkinson's Disease)
Background. Safinamide is a selective, reversible monoamine oxidase-B inhibitor with a sodium channel inhibitory effect. Published clinical evidence supports safinamide as an effective therapy for Parkinson’s disease (PD) with wearing-off. However, to date, no consensus recommendations have been available to guide physicians in Asia on the optimal use of safinamide in clinical practice. To summarize opinions on the optimal patient profile and methods of using safinamide in common clinical scenarios, Japanese movement disorder specialists with expertise in PD investigated the perspectives of neurologists and neurosurgeons. Methods. The Delphi panel approach was used to summarize the opinions of panelists. The panel comprised doctors from Japan with extensive clinical practice experience in the use of safinamide (n = 46 at the final round). The consensus was defined as 80% or more agreement between panelists for each scenario at the final round. Results. There was a high level of agreement that patients with the following symptoms are suitable for safinamide treatment such as bradykinesia (100%), rigidity (95.7%), and/or gait disorder (89.1%) based on motor symptoms and PD-related pain (97.8%) and/or depression or apathy (93.5%) based on non-motor symptoms. Morning-off (95.7%), but not dyskinesia (71.7%), also reached consensus. The use of high-dose safinamide (100 mg/day) was recommended when the improvement in PD symptoms is insufficient and increasing the doses of other anti-PD medications is difficult (97.8%) or when the abovementioned non-motor symptoms adversely affect daily life (93.5%). Conclusions. This report provides expert perspectives on the use of safinamide for a wide range of clinical scenarios in Japan.